2022
DOI: 10.1111/ijag.16579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local ion concentrations on the in vitro reactions of bioactive glass 45S5 particles

Abstract: Bioglass 45S5 is the most widely used bioactive glass composition in orthopedics to regenerate bone tissue. Although its reactions in vitro and in vivo are well established, the impact of the local environment on the dissolution behavior in the dynamic environment is not fully understood. Here, we show that the ion concentrations released from 45S5 into Tris-buffer solution and simulated body fluid (SBF) in a cascade system of three reactors in a series significantly differed depending on the ion concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…However, the current study demonstrated that the mineralization of the Ti surface by the Zn4-CaP layer resulted in a diminished antibacterial effect against S. mutans. The limited antibacterial effect can be explained by the low amount of unreacted glass left from the BG particles after the formation and mineralization of the Ca-P layer [37,38]. Although Zn4 has a lower dissolution rate than 45S5 BG, the SBF incubation time was long enough to convert the glass particles almost entirely into CaP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current study demonstrated that the mineralization of the Ti surface by the Zn4-CaP layer resulted in a diminished antibacterial effect against S. mutans. The limited antibacterial effect can be explained by the low amount of unreacted glass left from the BG particles after the formation and mineralization of the Ca-P layer [37,38]. Although Zn4 has a lower dissolution rate than 45S5 BG, the SBF incubation time was long enough to convert the glass particles almost entirely into CaP.…”
Section: Discussionmentioning
confidence: 99%